THE IMPORTANCE OF SONGS IN GUIDING THE YOUNG GENERATION TOWARDS NATIONAL VALUES - Sarsenbaeva , Uldawlet (Универсальная индексная библиотека Евразийского журнала социальных наук, философии и культуры, 2025)
This article explores the role of songs in guiding the younger generation toward national values, with particular reference to Karakalpak culture. It argues that songs are more than artistic expressions; they are cultural archives that preserve language, history, and moral lessons. Through folk songs, lullabies (Besik yir), and epic songs, youth are introduced to themes of patriotism, respect, unity, and bravery. The article also examines the emotional and educational functions of songs, showing how they shape identity and character. A comparative table illustrates the functions of different song types in shaping youth values.